2021
DOI: 10.1021/acsnano.0c08628
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore-Based Power Generation from Salinity Gradient: Why It Is Not Viable

Abstract: In recent years, the development of nanopore-based membranes has revitalized the prospect of harvesting salinity gradient (blue) energy. In this study, we systematically analyze the energetic performance of nanopore-based power generation (NPG) at various process scales, beginning with a single nanopore, followed by a multipore membrane coupon, and ending with a full-scale system. We confirm the high power densities attainable by a single nanopore and demonstrate that, at the coupon scale and above, concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 109 publications
2
131
0
1
Order By: Relevance
“…68,69 Although the focus here has been devoted to the understanding of osmotic transport across a single-pore membrane or channel, further challenges lie ahead of diffusio-osmosis in order to establish itself as a viable source of renewable energy, in particular, for what concerns the generation of electricity using multipore systems. 3,4,70 In conclusion, we have provided a unified description of osmotic transport by coupling first principles simulations with a mean field description of the EDL and with the Stokes equation of hydrodynamics, and have applied this framework to understand the osmotic transport properties of a prototypical salt that displays pronounced ion-specific effects on two-dimensional materials. Through the mPB equation of the EDL (see Eq.…”
Section: Discussionmentioning
confidence: 99%
“…68,69 Although the focus here has been devoted to the understanding of osmotic transport across a single-pore membrane or channel, further challenges lie ahead of diffusio-osmosis in order to establish itself as a viable source of renewable energy, in particular, for what concerns the generation of electricity using multipore systems. 3,4,70 In conclusion, we have provided a unified description of osmotic transport by coupling first principles simulations with a mean field description of the EDL and with the Stokes equation of hydrodynamics, and have applied this framework to understand the osmotic transport properties of a prototypical salt that displays pronounced ion-specific effects on two-dimensional materials. Through the mPB equation of the EDL (see Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This effect will be addressed in more detail in the following sections. 182,185 Although pore diameters comparable to l D could be thought of as a limiting constraint, some authors have reported interesting counter-examples. 119,186 Siria et al reported the development of a single boron nitride nanotube with an inner radius of 40 nm that achieved an extracted power density of 4 kW m À2 .…”
Section: Channel Diametermentioning
confidence: 99%
“…10(g)). 106,182,185 For this reason, the use of smaller nanochannels can be crucial for the development of up-scaled membranes. Furthermore, as described in the following sections, the use of heterogeneous membranes has been widely employed as an approach to reduce the mechanisms that vanish the output power harvested in membranes with high pore density.…”
Section: Pore-densitymentioning
confidence: 99%
“…Elucidating the molecular-level operation of RED membranes is necessary to advance practical implementation of this technology. In this context, establishing a connection between the surface charge density, membrane ion permselectivity, and conductance is crucial [28][29][30][31][32][33] . However, challenges remain because these traditional ionic membranes typically do not allow precise simultaneous control over the pore structure and ionic site population.…”
Section: Introductionmentioning
confidence: 99%